How are public sector organizations assessing their IT investments and benefits-An understanding of issues for Benchmarking - Liu, Y.; Lin, Chad (College of Informatics, Chaoyang University of Technology, 2008)
Despite the growing IT spending by public sector organizations, evaluation of IT investments still presents a major problem for these organizations. A survey of the top 500 Australian public sector organizations and the in-depth case studies of three Australian public sector organizations were conducted. The main purpose of the study was to examine the key issues of IT investment evaluation and benefits realization in public sector organizations. The results indicated that effective deployment of appropriate IT investment evaluation methodology and benefits realization methodology are critical to the successful outcomes for IT project. A number of key IT evaluation issues were also identified: user satisfaction, top management support, change management, and user involvement.